Welfare Assessment of Maleo Chicks in Hungayono Sanctuary, Bogani Nani Wartabone National Park, Gorontalo - F. R. Karim; B. Masy’ud; J. B. Hernowo (Faculty of Animal Science, Bogor Agricultural University, 2023)
The decline in the Maleo population due to the decrease in suitable nesting sites caused the need for Maleo conservation activities such as protecting Maleo’s nesting site and their eggs. This study aims to analyze aspects of Maleo chicks captive management and assess Maleo chicks welfare levels in Hungayono Sanctuary. The method used is direct observation, interviews, and literature studies. Data analysis was carried out by describing the welfare assessment. The results showed that welfare management in Hungayono includes the management of cages, feed, and health. Management activities for the aspects of cages, feed, and overall health are still lacking. This is because several important aspects had not been fulfilled in management, such as the quantity and quality of the cages, feed and water given, also medical personnel and facilities. Maleo chick’s welfare level in Hungayono had a value of 49.73, which was categorized as low. The aspect of freedom from pain, injury, and disease had the lowest score, which was 1.92. In conclusion, the overall management of maleo chick's in Hungayono was still lacking and needed to be improved. The welfare level of Maleo chick’s was low, with freedom from pain, injury, and disease having the lowest score. Hungayono managers need to add medical personnel and increase the quality and quantity of their medical facilities to improve the aspects of freedom from pain, injury, and disease.